SIS therapy in the treatment of distal radius epiphyseal fracture (Case report) (Balneo and PRM Research Journal, 2021)
Introduction. Fractures of the distal radius epiphysis are the most common fractures of the upper limb, present both in the general population active following major trauma and in the elderly population in minimal trauma due to osteoporosis. Among the adjuvant therapies for orthopedic treatment of distal radius epiphyseal fracture we can list Super Inductive System (SIS), a therapy based on the interaction between the electric field and the human body with the improvement of the healing process by acting on the pathophysiological stages of bone callus.Material and method. A clinical case study was performed on a 28-year-old patient, hospitalized and treated in the neurosurgery department of the Constanta County and Emergency Hospital for a polytrauma by road accident (passenger) with amyelotic cervical vertebral trauma, thoracic trauma and trauma to the right upper limb, subsequently performing 12 SIS therapy sessions at the Balneal and Rehabilitation Sanatorium of Techirghiol. CT examination of the cervical spine reveals fractures of C4 vertebra (the blade and pedicle) and C5 vertebra (vertebral body, lamina and pedicle). Right forearm radiography reveals fracture of the right radial styloid. After conservative treatment of the cervical injury and orthopedic treatment of the upper limb injury, the clinical evolution is favorable, allowing the patient to be discharged and allowed to do 12 sessions of SIS therapy, 3 times a week, within 4 weeks. The subsequent clinical and paraclinical evolution was favorable for the outpatient orthopedic ambulatory reevaluation performed at 5 weeks.Results and discussions.  Due to the type of fracture of the radial distal epiphysis (linear fracture without displacement), absence of comorbidities and young age, led to the indication of orthopedic treatment with immobilization in the antebrachio-palmarcast, which allowed subsequent physiotherapy.
Keywords: radial fracture; callus; polytrauma; cervical spine; lamina; Super Inductive System